Fermented dairy product consumption and blood lipid levels in healthy adults: a systematic review - Yilmaz, Birsen; Alvanoudi, Panagiota; Kalogeropoulou, Aggeliki; Santa, Dushica; Bulmuş-Tüccar, Tuğçe; Nikolaou, Anastasios; Moreno-Indias, Isabel; Ruiz-Limon, Patricia; Gutiérrez-Repiso, Carolina; Hillesheim, Elaine; Meslier, Victoria; Mayo, Baltasar; et al. (Frontiers Media SA, 2025)
Systematic review registration osf.io/h2mbe/